Immune response of intestinal micrornas to transport stress in hybrid yellow catfish (tachysurus fulvidraco♀ ×t. vachellii♂) : response strategy and potential biomarker - Tao Zheng; Yifan Tao; Siqi Lu; Jun Qiang; Pao Xu (BMC Genomics)
Abstract Fish transportation, a routine operation in aquaculture, can induce immune responses in fish, potentially affecting their health. Nevertheless, the immune response mechanisms involved in microRNAs (miRNAs) under transport stress remain unclear. Therefore, we investigated the immune response strategy of miRNAs in intestines of hybrid yellow catfish under transport stress via physiological, biochemical and RNA-seq analysis. We found that transportation induced innate immune response of intestines characterized by significant increases in alkaline phosphatase, acid phosphatase, lysozyme, and complement 3 level. Meanwhile, 50 differentially expressed miRNAs were identified and comprehensive analysis of miRNA-mRNA sequencing showed their targets genes involved in 9 immune-related pathways. Notably, the miRNAs involved in immune regulation, such as miR-29a/b, miR-106, miR-454-3p and miR-455, were notably upregulated following the induction of transport stress, while miR-196a-5p was significantly downregulated. In addition, their corresponding target genes such as tkt, mafg, arap2, nfatc2, egr2 and wnk4 showed opposite expression trends, suggesting that these genes may be the key immunomodulatory targets of corresponding miRNA. Here, we focused on the regulatory function of miR-455 and its predictive target genes egr2. Double luciferase assay revealed that miR-455 might exist binding site in the 3’-UTR sequence of egr2 mRNA. Interestingly, silencing miR-455 under transport stress led to the increase of intestinal egr2 expression, affected intestinal immune and inflammation responses, and caused intestinal tissue damage and abnormal secretion of mucous substances. In conclusion, transport stress triggered intestinal immune response, and multiple miRNAs played important role in immune response, among which miR-455 might be an important biomarker. These findings not only improve the understanding of the immunomodulatory function of miRNA in fish, but also provide a theoretical basis for screening potential regulatory targets under transport stress. Graphical abstract